In(OTf)3 catalysed an expeditious synthesis of β-carboline–imidazo[1, 2-a]pyridine and imidazo[1, 2-a]pyrazine conjugates. Issue 50 (3rd May 2016) - Devi, Nisha; Singh, Dharmender; Honey,; Mor, Satbir; Chaudhary, Sandeep; Rawal, Ravindra K.; Kumar, Vipin; Chowdhury, Asim K.; Singh, Virender
Abstract : β-Carboline containing alkaloids are ubiquitously present in Nature, while an imidazo[1, 2- a ]pyridine nucleus is incorporated in various synthetic commercial drugs and biologically previliged moieties. Abstract : β-Carboline containing alkaloids are ubiquitously present in Nature, while imidazo[1, 2- a ]pyridine nucleus is incorporated in various synthetic commercial drugs and biologically previliged moieties. On this basis, new β-carboline–imidazoazine conjugates were designed and a small library of compounds integrating both the pharmacophores was constructed with 4-points of diversity by using the In(OTf)3 assisted Groebke–Blackburn–Bienayme multicomponent strategy. The methodology was found to be simple and convenient for the efficient syntheses of β-carboline–imidazo[1, 2- a ]azine conjugates. The present synthetic protocol provides several advantages like operational simplicity, appreciable atom economy, short reaction time and easy purification procedure.